Structures and functions of the normal and injured human olfactory epithelium - Kikuta, Shu; Nagayama, Shin; Hasegawa-Ishii, Sanae (Frontiers in Neural Circuits, 2024)
The olfactory epithelium (OE) is directly exposed to environmental agents entering the nasal cavity, leaving OSNs prone to injury and degeneration. The causes of olfactory dysfunction are diverse and include head trauma, neurodegenerative diseases, and aging, but the main causes are chronic rhinosinusitis (CRS) and viral infections. In CRS and viral infections, reduced airflow due to local inflammation, inflammatory cytokine production, release of degranulated proteins from eosinophils, and cell injury lead to decreased olfactory function. It is well known that injuryinduced loss of mature OSNs in the adult OE causes massive regeneration of new OSNs within a few months through the proliferation and differentiation of progenitor basal cells that are subsequently incorporated into olfactory neural circuits. Although normal olfactory function returns after injury in most cases, prolonged olfactory impairment and lack of improvement in olfactory function in some cases poses a major clinical problem. Persistent inflammation or severe injury in the OE results in morphological changes in the OE and respiratory epithelium and decreases the number of mature OSNs, resulting in irreversible loss of olfactory function. In this review, we discuss the histological structure and distribution of the human OE, and the pathogenesis of olfactory dysfunction associated with CRS and viral infection.